Evaluation of the accuracy of a mobile and a stationary system for three-dimensional facial scanning. Issue 10 (October 2016) - Modabber, Ali; Peters, Florian; Kniha, Kristian; Goloborodko, Evgeny; Ghassemi, Alireza; Lethaus, Bernd; Hölzle, Frank; Möhlhenrich, Stephan Christian
Abstract: Purpose: Numerous three-dimensional (3D) facial scanners have emerged on the market; however, publications evaluating their accuracies are sparse. In this study, the accuracy of two 3D scanners used in facial scanning was evaluated. Materials and methods: A test specimen was attached at the right cheek and the forehead of 41 volunteers. These volunteers were scanned with Artec EVA ® and FaceScan3D ® . The acquired data were aligned to a 3D model of the test specimen for comparing the mean error, original length and width and angles to the measured values. Results: The mean error in Best Fit alignment is significantly lower using Artec EVA ( p < 0.001) for both test specimens. The deviation from the original length and width is significantly lower for the test specimens ( p < 0.01) when measured with Artec EVA. The aberration of the angles measured between the front plane and the side plane is significantly lower when measured with Artec EVA ( p < 0.001). Captured with Artec EVA the discrepancy between the original angle and the angle measured between the side planes to each other is significantly lower ( p < 0.01). Conclusions: Scanning with Artec EVA leads to more accurate 3D models as compared to scanning with FaceScan3D. The exactness achieved by both scanners is comparable to other scanners mentioned in literature.